Validation of the Spanish Center for Epidemiological Studies Depression and Zung Self-Rating Depression Scales: a comparative validation study. - Paulo Ruiz-Grosso (Public Library of Science (PLoS), 2012)
Background Depressive disorders are leading contributors to burden of disease in developing countries. Research aiming to improve their diagnosis and treatment is fundamental in these settings, and psychometric tools are widely used instruments to support mental health research. Our aim is to validate and compare the psychometric properties of the Spanish versions of the Center for Epidemiological Studies Depression Scale (CES-D) and the Zung Self-Rating Depression Scale (ZSDS). Methodology/principal findings A Spanish version of the CES-D was revised by 5 native Spanish speaking psychiatrists using as reference the English version. A locally standardized Spanish version of the ZSDS was used. These Spanish versions were administered to 70 patients with a clinical diagnosis of DSM-IV Major Depressive Episode (MDE), 63 without major depression but with clinical diagnosis of other psychiatric disorders (OPD), and 61 with no evidence of psychiatric disorders (NEP). For both scales, Cronbach's alpha (C-α) and Hierarchical McDonald Omega for polychoric variables (MD-Ω) were estimated; and receiver operating characteristics (ROC) analysis performed. For the CES-D and ZSDS scales, C-α was 0.93 and 0.89 respectively, while MD-Ω was 0.90 and 0.75 respectively. The area under the ROC curve in MDE+OPD was 0.83 for CES-D and 0.84 for ZSDS; and in MDE+NEP was 0.98 for CES-D and 0.96 for ZSDS. Cut-off scores (co) for the highest proportions of correctly classified (cc) individuals among MDE+OPD were ≥29 for CES-D (sensitivity (ss) = 77.1/specificity (sp) = 79.4%/(cc) = 78.2%) and ≥47 for ZSDS (ss = 85.7%/sp = 71.4%/cc = 78.9%). In the MDE+NEP, co were ≥24 for the CES-D (ss = 91.4%/sp = 96.7%/cc = 93.9%) and ≥45 for the ZSDS (ss = 91.4%/sp = 91.8%/cc = 91.6%). Conclusion Spanish versions of the CES-D and ZSDS are valid instruments to detect depression in clinical settings and could be useful for both epidemiological research and primary clinical settings in settings similar as those of public hospitals in Lima, Peru.